592=2L+2(5L+6)

Simple and best practice solution for 592=2L+2(5L+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 592=2L+2(5L+6) equation:


Simplifying
592 = 2L + 2(5L + 6)

Reorder the terms:
592 = 2L + 2(6 + 5L)
592 = 2L + (6 * 2 + 5L * 2)
592 = 2L + (12 + 10L)

Reorder the terms:
592 = 12 + 2L + 10L

Combine like terms: 2L + 10L = 12L
592 = 12 + 12L

Solving
592 = 12 + 12L

Solving for variable 'L'.

Move all terms containing L to the left, all other terms to the right.

Add '-12L' to each side of the equation.
592 + -12L = 12 + 12L + -12L

Combine like terms: 12L + -12L = 0
592 + -12L = 12 + 0
592 + -12L = 12

Add '-592' to each side of the equation.
592 + -592 + -12L = 12 + -592

Combine like terms: 592 + -592 = 0
0 + -12L = 12 + -592
-12L = 12 + -592

Combine like terms: 12 + -592 = -580
-12L = -580

Divide each side by '-12'.
L = 48.33333333

Simplifying
L = 48.33333333

See similar equations:

| 2(-1)+9= | | 12x+9=9x-18 | | 4x-5=3-7x | | 48=4(x+10) | | 4u^2-4=15 | | 5v+7=6v-11 | | 6x=5x+16 | | 16(x+3)-4x=4(3x+2)-12 | | 5(3x-7)-(3x+9)= | | 19-u=238 | | -8(b-5)=-2(b+1) | | a-3[b-2(c-x)]=4 | | 167=2(3w-5)+2w | | 3x+6=9(x+4) | | 3(6p+5)=21 | | 3x+6=9(x+9) | | 7(4x+7)=6(1+x)-1 | | 2e^3x-2=7 | | C-13=5(3) | | 40=8(n-2) | | -5(8x+4)=-140 | | c=49.99-.25*49.99 | | 4[8-(-9x-1)]=180x+52 | | 3y-10x=-45 | | 5(4x-3)=15 | | x=(4y-9)(6y-7) | | 5+x=4(8) | | y+8=3(x+15) | | 70619.542=2*3.14*1303.21+2*3.14*36.1*h | | 2+4sinx=0 | | 422.67=c+.15c | | -(-4x+10-8y)= |

Equations solver categories